Uso de palmilha postural na correção do valgo dinâmico do joelho de atletas amadores de esportes de giro e salto: ensaio clínico aleatorizado - Mendes, Heber Alves de Sousa (2022)
Introduction: Estimated knee valgus (VDJ) that is generated by joint misalignment, changes in plantar pressure distribution points. The Insole can be an alternative for postural and posterior adjustment. Objective: To analyze the effect of the use of postural insole in the correction of the VDJ of amateur athletes of turning and jumping sports. Materials and Method: This is a randomized controlled clinical trial, carried out with 16 male amateur athletes, age (12 - 23 years), height (1.81 - 1.57 m), body mass (44.1 - 70.3kg) and BMI (6.0 – 26.0) with VDJ and foot promotion, randomly distributed into 2 groups: Corrective Postural Insole Group (gPPC) and Placebo Postural Insole Group (gPPP). Data collection, were the markers of reflective indicators in the lower and middle limbs: the project of step projection in the knee plane (APantropo do knee, by video capture during LSD) associated with the Excursion Index of the Pressure data (CPEI) of the foot, by Computerized Baropodometry (BPC) in non-symptomatic patients. Results: Significant differences were observed between the means obtained in the APPF assessments of the gPPP group (P=0.005) and the gPPC (P=0.049), whereas the means of the IECP assessments in both groups were not significant (P>0, 05). Conclusions: The findings allow us to conclude that the use of postural insoles, without or with corrective shims, showed similar improvements in the treatment of VDJ, since they provided the same increase in APPF (more than 6º), thus, the use of postural insoles, in this study, it was not shown to be effective in reducing the VDJ.